2021
DOI: 10.1051/e3sconf/202128005007
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Ukraine’s energy system: challenges under high renewable energy penetration and the COVID-19 pandemic

Abstract: The paper deals with the problems of balancing the United Energy System of Ukraine caused by high renewable energy penetration and the impact of the COVID-19 pandemic on the energy sector. The paper analyses the trends in renewable energy development, the dynamics and structure of electricity consumption and export in pre-epidemic and epidemic periods and identifies the main challenges to operational security of the United Energy System of Ukraine. The methodical approach to improve the methodology for estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…As of 2022, hydropower, solar, and wind energy plants provided nearly 85% of all renewable electricity production. A significant increase in renewable electricity production will specifically require bioenergy that has considerable potential and can significantly contribute to achieving that goal (Kurbatova et al, 2019;Kurbatova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As of 2022, hydropower, solar, and wind energy plants provided nearly 85% of all renewable electricity production. A significant increase in renewable electricity production will specifically require bioenergy that has considerable potential and can significantly contribute to achieving that goal (Kurbatova et al, 2019;Kurbatova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This model should be dynamic and flexible, providing mechanisms for adjusting the tools depending on the conditions that arise in society. In particular, the practice has shown that "green" tariffs, which were relevant at the initial stages of the development of renewable energy, should be mixed with other instruments and accompanied by tools for balancing energy production and developing energy storage systems (Kurbatova et al, 2019(Kurbatova et al, , 2021Sotnyk et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Grzanic et al [25] and Gopinathan N. et al [26] analyzed models and opportunities for prosumers with PV installations, EVs, power storage, and other flexible devices. Several studies [25,[27][28][29][30] have examined different types of aggregation of individual prosumers: energy communities or microgrids, combined market participation, and decentralization models to stimulate internal energy exchange and solve local grid problems. Market participation models for prosumers relying on smart grid technologies through peer-to-peer (p2p) trading, self-dispatching zones, virtual power plants, EV demand response, etc., were investigated by Grzanic M. et al [25], Junlakarn S. et al [31], 2022, and Kelm P. et al [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The long-term application of FIT to support RESs in Ukraine certainly played an essential role in the rapid growth of their installed capacity, particularly domestic SPPs and wind turbines. However, the shortcomings of this system and the need to transition to alternative pricing systems and support methods are discussed in [11,12,29,49,50]. In addition to the general regulatory barriers for producers of RESs in Ukraine, such as the impossibility of independent participation in the market for bilateral contracts outside the balancing group of the state enterprise "Guaranteed Buyer", the introduction of contracts for difference, market barriers to participation in any segment of the electricity market, responsibility for imbalances, etc., there are barriers specifically for small and household RESs, as well as prosumers.…”
Section: Prosumers: Regulatory Constraintsmentioning
confidence: 99%
“…Specifically, in the context of global challenges, such as the COVID-19 pandemic, climate change, military aggression, and the development of electro mobility, the introduction of digital technologies in the accounting of the fuel and energy sector will allow for a faster and more efficient response to changes in the economic environment and optimal accounting policies [8][9][10]. For example, digital technologies can be used to quickly track changes in market conditions and changes in the relevant legal framework, which will reduce the cost of responding to and adapting to changes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%